Business Process Modeling of a Web-Based Learning System for Annual Tax Return Reporting Using the Coretax Administration System Model - Mufida, Farah Ayu; Eltivia, Nurafni; Djajanto, Ludfi (Dinasti International Journal of Economics, Finance & Accounting, 2025)
The application of information technology in tax education is a strategic effort to enhance students' understanding and skills in tax reporting. This study aims to design a Business Process Model using the Business Process Model and Notation (BPMN) method for a web-based learning system of Annual Tax Return (SPT) reporting, based on the Coretax Administration System (CTAS) model, and implemented at the Tax Laboratory of Politeknik Negeri Malang. The research employs a descriptive qualitative method, with data collected through literature review, user needs analysis, and business process modeling. The resulting BPMN diagrams successfully simulate key components of real tax reporting processes, including taxpayer registration, digital certificate requests, and the submission of both individual and corporate SPTs. These business process models enable students to better understand and visualize digital tax workflows, thereby bridging the gap between theoretical concepts and practical systems. The models are expected to support the modernization of tax education in vocational higher education institutions.